The European Monetary System: Deficits and Cures - Henning Bohn; Otmar Issing; Frank Westermann (ifo Schnelldienst, 2016)
– Vorträge von Prof. Henning Bohn Professor of Economics, University of California, Santa Barbara, Prof. Dr. Dr. h.c. mult. Otmar Issing President Center for Financial Studies, Uni-versity of Frankfurt, und Prof. Dr. Frank Westermann Professor of Economics, University of Osnabrück
Keywords: F33; F34; G01; E42; 330; Währungsunion; Europäisches Währungssystem; Eurozone